THE EFFECTS AND EFFICIENCY OF HEARING STORIES ON VOCABULARY ACQUISITION BY STUDENTS OF GERMAN AS A SECOND FOREIGN LANGUAGE IN JAPAN - Beniko Mason; Martina Vanata; Katrin Jander; Ramona Borsch; Stephen Krashen (Indonesian JELT, 2009)
The usual approach to vocabulary learning is to present students with a list of words to be memorized, present them in the context of a text, and then provide exercises to “reinforce” the vocabulary. The purpose of these studies with beginning level German-as-a-foreign language university students in Japan was to determine whether beginning level students with limited vocabulary in German could sustain their interest in hearing a story for over 20 minutes, and to determine how much vocabulary could be gained just from hearing stories, without a list to memorize and supplementary vocabulary exercises. The first experiment showed that hearing a story had a higher acquisition/learning rate than a list method. The second and third experiments showed that supplementary focus on form activities were not worthwhile on vocabulary acquisition/learning, and that the rate of acquisition/learning was .10 words per minute during the seven weeks. It appears to be the case that students acquire six words per hour when they hear stories, while they learn 2.4 words per hour in traditional classes. Keywords:    German-as-a-foreign language; vocabulary exercises; acquisition/learning rate; focus on form